Identification and characterization of a new potyvirus infecting cucurbits - Perotto, Maria Cecilia (2018)
A new potyvirus, tentatively named cucurbit vein banding virus (CVBV), was identified in crops of cucurbits in San Pedro (Buenos Aires, Argentina). The complete genome sequences of two isolates of CVBV were obtained by next-generation sequencing (Illumina). The genomic RNA consisted of 9968 and 9813 nucleotides, respectively, and displayed typical potyvirus organization. The percentage identity for these two genome sequences, using BLASTn, was 77% to sweet potato virus c and 73% to tomato necrotic stunt virus. BLASTx analysis of the complete polyprotein showed that the most closely related virus is plum pox virus, with 48% amino acid sequence identity for both isolates. Sequence comparisons and phylogenetic analyses indicate that CVBV belongs to a previously undescribed species in genus Potyvirus.